The physiology of yoga - McGonigle, Andrew; Huy, Matthew P. 1979-
"This book explains how each of the body's internal systems is affected and enhanced by a consistent yoga practice. It allows the serious or curious yogi to better understand how yoga provides myriad benefits for the body and mind. It also encourages readers to engage in critical thinking when evaluating claims about what yoga can do. Chapters cover the musculoskeletal, nervous, respiratory, cardiovascular, lymphatic, immune, endocrine, reproductive, and digestive systems of the body. A final chapter provides practical application with four sample yoga practices"--